The role of administrative court in ensuring human rights protection under martial law - Aurika Paskar (Eastern Journal of European Studies, 2023)
The article explores the peculiarities of administrative jurisdiction during martial law and its role in safeguarding human rights through judicial protection. It delves into the specific legal regulations governing court activities in such circumstances, highlighting the challenges in protecting human rights. The collaborative mechanisms between courts and judicial self-government bodies are revealed, focusing on ensuring access to justice during martial law. The administrative court's pivotal role in human rights protection is emphasized, along with the disclosed mechanisms for facilitating administrative justice accessibility in martial law situations. The article also addresses the standards of access to justice, examining their implementation in administrative proceedings and analysing measures introduced to support court functionality. Importantly, it underscores that even in the most challenging conditions, the administrative court must leverage its powers to uphold constitutional rights and human freedoms. Beyond the immediate martial law context, the research subtly highlights the broader implications of digitalization in legal processes. The seamless integration of video conferencing not only ensures unimpeded access to justice but also showcases the transformative influence of technology on legal frameworks. The authors' insightful analysis makes a valuable contribution to the ongoing discourse on the benefits of digitalization in legal practices.